The Anthropology of Latin America and the Caribbean - Sanabria, Harry.
1 online resource.
Keywords: This wide-ranging introduction to the anthropology of Latin America and the Caribbean offers broad coverage of culture and society in the region, taking into account historical developments as well as the roles of power and inequality. The chapters address key topics such as colonialism, globalization, violence, religion, race and ethnicity, gender and sexuality, health, and food, and emphasize the impact of Latin American and Caribbean peoples and cultures in the United States. The text has been thoroughly updated for the second edition, including fresh case studies and new chapters on independence, neoliberalism and immigration, and popular culture and the digital revolution. Students are provided with a solid overview of the major contemporary trends, issues, and debates in the field. Each chapter ends with a summary, up-to-date recommendations for viewing films/videos and websites, and a comprehensive bibliography for further reading and research.